Implementasi Kebijakan Pelayanan Obstetri dan Neonatal Emergency Dasar (PONED) di Puskesmas Kabupaten Solok - Tuty Ernawati; Sri Siswati; Luthfil Hadi Anshari (LPPM Hang Tuah Pekanbaru, 2023)
The mortality rate of mother infants in West Sumatra is very high, with a mother mortality rate of 12, an infant mortality rate of 15, and a neonatal mortality rate of 71 in 2020. This indicates that emergency obstetrics and neonatal care practices are not yet optimal. (PONED) is located at a PONED-compatible health center. The purpose of this study is to analyze the implementation of PONED program services at health centers. The survey method used the descriptive qualitative method conducted from March to October 2021, with deep interviews, document reviews, observation-based data collection, and seven information providers. KIA, District Program, PONED Health Center, 4 people, analysis using data content technology Analysis by triangulation. The implementation of PONED-enabled public health center guidelines is not optimal and still being implemented by the health sector, starting with preparations for the selection of PONED health centers, resources, or PONED. Provides availability for teams, infrastructure, equipment, medicines, and consumables. Engagement, stakeholder communication, and community socialization processes were not optimal. A unified referral system that plays an important role in implementing PONED, including budget awareness, coordination, stakeholder involvement, and comprehensive neonatal emergency obstetric services at professional associations, NGOs, communities, and hospitals. This requires good cooperation and support from local governments. In summary, the implementation of the PONED Health Center program is not optimal, and maternal, infant, and newborn deaths are still recorded. Therefore, there is an urgent need to assist local governments and stakeholders by providing resources in accordance with PONED implementation requirements at health centers